Studi Komparatif Efektifitas Model Pembelajaran Klinik One Minute Preceptor (Omp) Dan Snapps Terhadap Pencapaian Kompetensi Mata Kuliah Kepemimpinan Dan Manajemen Keperawatan Mahasiswa Profesi Ners Fkep Unand - Setiadi Syarli; Yulastri Arif; Rika Fatmadona; Larasuci Arini (Jurnal Keperawatan Muhammadiyah, 2020)
Introduction: The problem that is happening right now is the level of national nurse competency test passing which is currently still low. Various factors are believed to influence, among others, clinical learning strategies that are ineffective and do not meet the different learning needs such as in leadership and nursing management subjects. Various effective models have been studied and developed including the One Minute Preceptor (OMP) mode and SNAPPS. Objective: to assess and compare the effectiveness of the OMP and SNAPPS models on the achievement of students' cognitive, affective, psychomotor and critical thinking competencies in the nursing management phase. Method: quasi-experiment with pretest and posttest group design. Total sampling (n = 13) and grouped n1 = 6 (OMP) and n2 = 7 (SNAPPS). Data analysis with paired t-test and independent t-test. Results: There were differences in the mean of competence (P <0.05) before and after the OMP treatment (cognitive; 18.3, affective; 7.8, critical thinking; 11.6) and SNAPPS (cognitive; 19.28, affective; 3.14, critical thinking; 5.0. There is a difference (P <0.05) the difference between the average competence before and after the treatment of OMP and SNAPPS (cognitive; 21,31 and 20,35) and (critical thinking: 0,96 and 7,61) Conclusion: OMP clinical learning model is considered more effective in the cognitive domain, critical thinking and psychomotor while the SNAPPS model is effective in the affective domain